2014
DOI: 10.1073/pnas.1408378111
|View full text |Cite
|
Sign up to set email alerts
|

Early remodeling of the neocortex upon episodic memory encoding

Abstract: Understanding the mechanisms by which long-term memories are formed and stored in the brain represents a central aim of neuroscience. Prevailing theory suggests that long-term memory encoding involves early plasticity within hippocampal circuits, whereas reorganization of the neocortex is thought to occur weeks to months later to subserve remote memory storage. Here we report that long-term memory encoding can elicit early transcriptional, structural, and functional remodeling of the neocortex. Parallel studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
80
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(92 citation statements)
references
References 55 publications
(86 reference statements)
8
80
1
1
Order By: Relevance
“…Thus, it is not surprising that BA44 might show extensive involvement in the brain's adaptation to the visual-motor adaptation task. That an area of cerebral cortex should be involved early in the learning process is consistent with recent work by Bero et al (55).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it is not surprising that BA44 might show extensive involvement in the brain's adaptation to the visual-motor adaptation task. That an area of cerebral cortex should be involved early in the learning process is consistent with recent work by Bero et al (55).…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, contextual fear memory consolidation can elicit early transcriptional, structural, and functional remodeling of PFC cells few hours after conditioning (Vetere et al, 2011;Bero et al, 2014). These observations are consistent with the demonstration that PFC neurons are reactivated during encoding of associative memories (Lesburgue`res et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…A possible mechanism involves the synthesis of new proteins required for strengthening synaptic connections in fear-related circuits. In addition, microstructural changes (Sandku¨hler and Lee, 2013) and activity-dependent gene expression have particular time-courses during memory consolidation (Bero et al, 2014;Aceti et al, 2015). These findings suggest that post-learning ''sensitive" periods are windows of opportunity during which traumatic memories can be manipulated.…”
Section: Introductionmentioning
confidence: 92%
“…Bero et al found that optogenetic excitation of mPFC neurons inhibits the activation of entorhinal-hippocampal circuits and impairs the encoding of long-term associative memory (Bero et al, 2014). Since the development of optogenetics, there have also been some new discoveries about the mechanism of memory retrieval.…”
Section: Alzheimer's Diseasementioning
confidence: 99%